2015
DOI: 10.1039/c5ob00078e
|View full text |Cite
|
Sign up to set email alerts
|

A modular synthesis of functionalised phenols enabled by controlled boron speciation

Abstract: A modular synthesis of functionalised biaryl phenols from two boronic acid derivatives has been developed via one-pot Suzuki-Miyaura cross-coupling, chemoselective control of boron solution speciation to generate a reactive boronic ester in situ, and oxidation. The utility of this method has been further demonstrated by application in the synthesis of drug molecules and components of organic electronics, as well as within iterative cross-coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Protecting group removal reveals the latent boronic acid, which can then be further reacted. Alternatively, in situ hydrolysis/Suzuki–Miyaura cross-coupling methods of BMIDA species have been developed. , We have recently shown that the direct generation of BPin esters can be achieved by control of the solution speciation during cross-coupling of monoprotected diboron (BPin/BMIDA) systems (Scheme b) . This directly provides a moderately reactive boronic ester product and avoids postreaction protecting group manipulation as well as facilitating the first approach to chemoselective sequential Suzuki–Miyaura cross-coupling using dielectrophile/dinucleophile systems. , Based on their increased versatility, direct access to boronic acids via manipulation of diboron systems during cross-coupling would be a valuable addition to the chemical toolbox and would present significant opportunities for the development of multibond forming tandem reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Protecting group removal reveals the latent boronic acid, which can then be further reacted. Alternatively, in situ hydrolysis/Suzuki–Miyaura cross-coupling methods of BMIDA species have been developed. , We have recently shown that the direct generation of BPin esters can be achieved by control of the solution speciation during cross-coupling of monoprotected diboron (BPin/BMIDA) systems (Scheme b) . This directly provides a moderately reactive boronic ester product and avoids postreaction protecting group manipulation as well as facilitating the first approach to chemoselective sequential Suzuki–Miyaura cross-coupling using dielectrophile/dinucleophile systems. , Based on their increased versatility, direct access to boronic acids via manipulation of diboron systems during cross-coupling would be a valuable addition to the chemical toolbox and would present significant opportunities for the development of multibond forming tandem reactions.…”
mentioning
confidence: 99%
“…For example, further Suzuki–Miyaura reactions using sp 2 - and sp 3 -hybridized electrophiles provided 9a and 9g , respectively in excellent yield. 9g can be readily converted to the parent compound 6 using existing methods . Chan–Evans–Lam coupling provided the morpholine derivative 9b in 78% yield while Hayashi-type 1,4-addition efficiently delivered 9c in 74% yield.…”
mentioning
confidence: 99%
“…Phenols are quite important molecules applied in organic chemistry as synthetic intermediates in the preparation of pharmaceuticals, agrochemicals and polymers. [1][2][3][4][5] Observing the immense value of phenols, scientists have tried to synthesize them through various reaction pathways. Traditional methods used for phenols preparation include the transition-metal-catalysed hydroxylation of aryl halides with hydroxide salts (e. g., KOH and NaOH) as well as nucleophilic aromatic substitution of activated aryl halides.…”
Section: Introductionmentioning
confidence: 99%
“…Phenols are quite important molecules applied in organic chemistry as synthetic intermediates in the preparation of pharmaceuticals, agrochemicals and polymers …”
Section: Introductionmentioning
confidence: 99%
“…We initiated the optimization study (Table 1) using triflate 1a with excess vinyl BPin. Employing conditions previously established in our group, [21][22][23][24][25] the Suzuki-Miyaura event proceeded rapidly and quantitatively, delivering Dane's diene (2a) as an intermediate. 26,27 We believed thermal promotion would enable cyclization, and a temperature screen indicated that a minimum of 150 °C (Table 1, entries 1-4) was necessary to drive the DA reaction to completion; 5 equivalents of vinyl BPin were required to overcome organoboron degradation and offset a competing homo DA consuming diene intermediate 2a (Table 1, entries 6-8).…”
mentioning
confidence: 99%